Low dietary vitamin E intake is associated with high risk of incident dementia among older adults: The Shanghai Aging Study - Liu, Su; Luo, Jianfeng; Xiao, Zhenxu; Wu, Wanqing; Liang, Xiaoniu; Ding, Saineng; Zhao, Qianhua; Zhao, Xianfeng; Wang, Yi; Ding, Ding (Frontiers in Nutrition, 2022)
Background: Growing evidence has shown the association between vitamin E intake and the risk of cognitive decline, but the conclusions were inconsistent. This study aimed to verify the hypothesis that vitamin E intake is associated with incident dementia and deterioration of global cognition. Methods: We followed 1550 non-demented community residents aged ≥60 years for an average of 5.2 years in the Shanghai Aging Study. Baseline vitamin E intake was measured by the Food Frequency Questionnaire. Cognitive function was evaluated by a battery of neuropsychological tests. A consensus diagnosis of incident dementia was made based on the DSM-IV criteria. Results: During the follow-up, 135 cases (8.7%) of incident dementia were identified. The incidence rates of dementia in low, low-medium, medium-high, and high vitamin E intake groups were 2.8, 1.5, 1.6, and 0.7 per 100 person-years, respectively (P<0.001). Participants with low vitamin E intake had a significantly higher risk of incident dementia than those with higher intake (compared with the highest intake group: hazard ratio [HR] 2.34, 95% confidence interval [CI] 1.20-4.57) after adjusting for confounders. Vitamin E intake was negatively correlated to the rate of annual decline of Mini-Mental State Examination score with the adjustment of confounders (β= 0.019, p = 0.001). Conclusion: Vitamin E intake is negatively correlated with the risk of dementia in older adults. An appropriate high amount of vitamin E intake from the diet might be helpful to prevent future cognitive decline.